The Impact of Early Visual Deprivation on Spatial Hearing: A Comparison between Totally and Partially Visually Deprived Children - Cappagli, Giulia; Finocchietti, Sara; Cocchi, Elena; Gori, Monica (Frontiers in Psychology, 2017)
The specific role of early visual deprivation on spatial hearing is still unclear, mainly due to the difficulty of comparing similar spatial skills at different ages and to difficulty in recruiting young blind children from birth. In this study, the effects of early visual deprivation on the development of auditory spatial localization have been assessed in a group of seven 3-5 years old children with congenital blindness (light perception) or low vision (visual acuity less than 3/10 to 0.05/10), with the main aim to understand if visual experience is fundamental for the development of specific spatial skills. Our study led to three main findings: firstly, totally blind children performed overall worse compared to sighted and low vision children in all the spatial tasks performed; secondly, low vision children performed equal or even better than sighted children in the same auditory spatial tasks; thirdly, a correlation between spatial accuracy and visual acuity in the dynamic condition of the auditory localization task indicates that the more residual vision the better spatial performance. These results suggest that early visual experience has an important role in the development of spatial cognition, even when the visual input during the critical period of visual calibration is partially degraded like in the case of low vision children. Overall these results shed light to the importance of early assessment of spatial impairments in visually impaired children and early intervention to prevent the risk of isolation and social exclusion.